Using qualitative content analysis to understand the active ingredients of a parent-mediated naturalistic developmental behavioral intervention. (October 2021) - Frost, Kyle M; Russell, Kaylin; Ingersoll, Brooke
Although naturalistic developmental behavioral interventions have a sizable and growing evidence base for supporting the development of children on the autism spectrum, their active ingredients and mechanisms of change are not well understood. This study used qualitative content analysis to better understand the intervention process of a parent-mediated naturalistic developmental behavioral intervention. Caregivers completed weekly written reflection responses as they learned each intervention technique. These responses were coded, and code co-occurrences were examined to understand the relationship between implementation of specific intervention techniques and potential mechanisms of change according to caregiver observations. The responses were subsequently compared to a theoretical causal model derived from the intervention manual. Many responses were consistent with the intervention theory; however, some theoretical outcomes were not reported by caregivers, and caregivers described some potential mechanisms that were not explicitly stated in the intervention theory. Importantly, we found that individual techniques were associated with various mechanisms, suggesting that global measures of social communication may be insufficient for measuring context-dependent responses to individual intervention techniques. Our findings point to specific observable behaviors that may be useful targets of measurement in future experimental studies, and as indicators of treatment response in clinical settings. Overall, qualitative methods may be useful for understanding complex intervention processes. Lay abstract: Although naturalistic developmental behavioral interventions are supported by research for supporting the development of children on the autism spectrum, how they work is not well understood. This study reviewed parent reflection comments in a systematic way to better how one such treatment worked, when delivered by caregivers. Caregivers completed weekly written reflection responses as they learned how to use the treatment techniques. We studied these responses to understand caregiver perspectives on how their children responded to the techniques. The responses were then compared to a theory of how the treatment works. Many responses were consistent with the treatment theory; however, others were not. We found that individual techniques were associated with different child responses, suggesting that general measures of social communication may not measure these specific short-term changes. Our findings point to specific behaviors that may be useful to measure in future research, or useful as indicators of treatment response in clinical practice settings. Overall, qualitative methods may be useful for understanding complex treatment processes.